Polychlorinated biphenyls and terphenyls (Geneva, 1993)
Evaluates the vast body of evidence demonstrating serious threats to human and environmental health posed by polychlorinated biphenyls (PCBs). These chemicals, which are now ubiquitous in the environment, have been used commercially since 1930 as dielectric and heat-exchange fluids and in a variety of other applications. Over 1,300 studies were critically assessed. The book also contains a brief review of the limited data on polychlorinated terphenyls.